Natural Killer Cells in Hepatic Ischemia-Reperfusion Injury - Huang, Miao; Cai, Hao; Han, Bing; Xia, Yuhan; Kong, Xiaoni; Gu, Jinyang (Frontiers in Immunology, 2022)
Ischemia-reperfusion injury can be divided into two phases, including insufficient supply of oxygen and nutrients in the first stage and then organ injury caused by immune inflammation after blood flow recovery. Hepatic ischemia-reperfusion is an important cause of liver injury post-surgery, consisting of partial hepatectomy and liver transplantation, and a central driver of graft dysfunction, which greatly leads to complications and mortality after liver transplantation. Natural killer (NK) cells are the lymphocyte population mainly involved in innate immune response in the human liver. In addition to their well-known role in anti-virus and anti-tumor defense, NK cells are also considered to regulate the pathogenesis of liver ischemia-reperfusion injury under the support of more and more evidence recently. The infiltration of NK cells into the liver exacerbates the hepatic ischemia-reperfusion injury, which could be significantly alleviated after depletion of NK cells. Interestingly, NK cells may contribute to both liver graft rejection and tolerance according to their origins. In this article, we discussed the development of liver NK cells, their role in ischemia-reperfusion injury, and strategies of inhibiting NK cell activation in order to provide potential possibilities for translation application in future clinical practice.